Effect Of Genetic And Non-Genetic Factors On Age At First Fertile Service In Malvi Heifers - Kumar, Amit; Sharma, Harish; Tomar, S.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The data for the present investigation pertained to 409 observations of age at first fertile service (AFFS) on Malvi cattle maintained at Govt. Cattle Breeding Farm, Agar, District Shajapur (M.P.), covering a period of 48 years from 1962 to 2009 (both years inclusive). The least squares analysis of variance revealed the mean AFFS in these cows to be 1451.81±41.23 days and the trait was significantly affected by sire (P< 0.01), period (P< 0.01) and inbreeding (P< 0.05). Heritability estimates for AFFS was obtained as 0.56±0.26 and phenotypic correlation between AFFS and first dry period were positive and significant (P
Keywords: Malvi heifers; inbreeding; age at first fertile service; heritability; correlation